MTHFR C677T polymorphism is associated with methotrexate-induced myelopathy risk. (7th February 2017) - Juster-Switlyk, Kelsey; Smith, A. Gordon; Kovacsovics, Tibor; Stephens, Deborah; Glenn, Martha; Palmer, Cheryl Ann; Quigley, Edward P.; Kolb, Noah
Abstract : Myelopathy is a rare complication of methotrexate (MTX) therapy. 1 A polymorphism (C677T) in the folate enzyme methylenetetrahydrofolate reductase (MTHFR) gene is associated with MTX hematologic and hepatic toxicity. 2 We describe 3 cases of severe MTX myelopathy associated with the MTHFR C677T polymorphism.